Characterization of a processed cheese spread produced from fresh cheese (quesito antioqueño) (2016)
Processed products are made from mixes of fresh and ripened cheeses; the use of cheeses with a short shelf-life in the development of processed cheeses is an alternative for the dairy industry. A processed cheese spread was made using only a soft and fatty fresh cheese that had been stored for 25 days. The primary materials were the fresh cheese, water, and emulsifying salts (sodium citrate (E-331) and sodium phosphate (E-450)), using a STEPHAN® Universal Machine (UMSK 24E) with indirect vapor injection and equipped with rasping and cutting blades. The resulting cheese (A) was compared with a commercial cheese (B) for compositional, physicochemical, and sensorial characteristics. The cheeses were similar except for the fat in dry matter (FDM), with values of 54.50% and 47.21%, respectively. Sensorially, there were significant differences (P0.05) for firmness, viscosity, and flavor; however, the instrumental viscosity did not present significant differences (P0.05). Cheese A provided, in mg per 100 g of product, 935.823 for phenylalanine, 1003.070 for isoleucine, 2041.420 for leucine, 475.337 for methionine, 119.300 for tryptophan, and 758.347 for valine. Producing processed cheeses with only fresh cheese is possible, resulting in a product that is similar to others that are currently on the market with typical characteristics that are accepted by consumers.